An endo-aesthetic management of crown dilaceration in a permanent mandibular central incisor - Wankhade, Abhijit D (BMJ Publishing Group, 2013)
Traumatic injuries to primary dentition may result in a wide range of developmental disturbances to succedaneous permanent teeth. The prevalence of morphological disturbances, secondary to dental injuries in the primary dentition, ranges from 12% to 69%. One of the morphological disturbances are crown dilacerations which are defined as the displacement of a portion of the developing crown at an angle to the longitudinal axis of the tooth. The prevalence of crown dilaceration constitutes 3% of the total injuries in developing teeth and is usually because of intrusion or avulsion of their primary predecessors. The present article narrates a case of crown dilaceration of a permanent mandibular right central incisor with open apex and large periradicular pathosis and its endo-aesthetic management with 2 years of follow-up.